Thermal-Desorption Proton-Transfer-Reaction Quadruple-Interface Time-of-Flight Mass Spectrometry: Online Analysis of Organic Aerosol Using Single-Component Particles - Kei Sato; Sathiyamurthi Ramasamy; Satoshi Inomata; Yu Morino; Toshihide Hikida; Akio Shimono (Aerosol and Air Quality Research, 2022)
Abstract A proton transfer reaction-quadrupole interface time-of-flight mass spectrometer was combined with a hand-made thermal desorption (TD) instrument for real-time analysis of organic aerosol particles. Size-selected single-component organic particles were generated using a nebulizer combined with a differential mobility analyzer. We tested perfluoroalkoxy alkene (PFA) and copper tubing for the TD instrument. Higher signal intensities were observed when using PFA tubing, suggesting that wall deposition loss of vaporized semi-volatile organic compounds was suppressed when PFA tubing was used. Protonated molecules, [M + H]+, had the highest intensity in the mass spectrum of dialdehyde particles (i.e., terephthaldialdehyde), whereas ions formed by dehydration from protonated molecules, [M + H - H2O]+, had the highest intensities in the mass spectra of carboxylic acid particles (i.e., adipic, phthalic, and cis-pinonic acids) and alcohol particles (i.e., meso-erythritol). The mass spectra obtained for organic aerosol markers will be useful to interpret mass spectra measured for organic aerosol particles by TD-proton transfer reaction-mass spectrometry.